Photodynamic therapy with paclitaxel-encapsulated indocyanine green-modified liposomes for breast cancer - Ishizuka, Mariko; Kaibori, Masaki; Sumiyama, Fusao; Okamoto, Yoshiharu; Suganami, Akiko; Tamura, Yutaka; Yoshii, Kengo; Sugie, Tomoharu; Sekimoto, Mitsugu (Frontiers in Oncology, 2024)
Background: Photodynamic therapy (PDT) involves the administration of a photosensitizing agent and irradiation of light at an excitation wavelength that damages tumor cells without causing significant damage to normal tissue. We developed indocyanine green (ICG)-modified liposomes in which paclitaxel (PTX) was encapsulated (ICG-Lipo-PTX). ICG-Lipo-PTX accumulates specifically in tumors due to the characteristics of the liposomes. The thermal and photodynamic effects of ICG and the local release of PTX by irradiation are expected to induce not only antitumor effects but also cancer immunity. In this study, we investigated the antitumor effects of ICG-Lipo-PTX in breast cancer. Methods: The antitumor effects of ICG-Lipo-PTX were examined in xenograft model mice subcutaneously implanted with KPL-1 human breast cancer cells. ICG-Lipo-PTX, ICG-Lipo, or saline was administered intraperitoneally, and the fluorescence intensity was measured with a fluorescence imaging system (IVIS). Intratumor temperature, tumor volume, and necrotic area of tumor tissue were also compared. Next, we investigated the induction of cancer immunity in an allogeneic transplantation model in which BALB-MC mouse breast cancer cells were transplanted subcutaneously in the bilateral inguinal region. ICG-Lipo-PTX was administered intraperitoneally, and PDT was performed on only one side. The fluorescence intensity measured by IVIS and the bilateral tumor volumes were compared. Cytokine secretory capacity was also evaluated by ELISPOT assay using splenocytes. Results: In the xenograft model, the fluorescence intensity and temperature during PDT were significantly higher with ICG-Lipo-PTX and ICG-Lipo in tumor areas than in nontumor areas. The fluorescence intensity in the tumor area was reduced to the same level as that in the nonirradiated area after two times of irradiation. Tumor growth was significantly reduced and the percentage of necrotic area in the tumor was higher after PDT in the ICG-Lipo-PTX group than in the other groups. In the allograft model, tumor growth on day 14 in the ICG-Lipo-PTX group was significantly suppressed not only on the PDT side but also on the non-PDT side. In addition, the secretion of interferon-γ and interleukin-2 was enhanced, whereas that of interleukin-10 was suppressed, in the ICG-Lipo-PTX group. Conclusions: The PDT therapy with ICG-Lipo-PTX may be an effective treatment for breast cancer.